Potentiation by α and Inhibition by β-Adrenergic Stimulations of Rat Platelet Aggregation - Yu, S. K; Latour, J. G (Thrombosis and Haemostasis, 1977)
Epinephrine, known to potentiate and elicit aggregation of human platelets, was shown to inhibit thrombin-induced aggregation of rat platelets, delaying the onset of aggregation from 2 to 12 times. Incubation of rat platelet suspensions with propranolol (1.25–30 μM), inactive by itself, totally prevented the inhibitory effect of epinephrine and also permitted a potentiation effect to show up. On the contrary, phentolamine (1.25–30 μM) potentiated the inhibitory effect of epinephrine on rat platelets and unmasked an inhibitory effect on human platelets. Finally, isoproterenol (0.25–9 μM) produced a marked inhibition of aggregation induced by thrombin, ADP and collagen in the three species studied, but most particularly in the rat. From these results, we conclude that stimulation of the platelet adrenergic receptors may either result in promotion (α-stimulation) or inhibition (β-stimulation) of platelet aggregation. Furthermore, differences in the ratios or responses of α/β receptors may account for species variations in the platelet aggregation response to catecholamine challenge.